Reactivation of Mutant p53 through Interaction of a C-Terminal Peptide with the Core Domain - Selivanova, Galina (American Society for Microbiology, 1999)
A synthetic 22-mer peptide (peptide 46) derived from the p53 C-terminal domain can restore the growth suppressor function of mutant p53 proteins in human tumor cells (G. Selivanova et al., Nat. Med. 3:632–638, 1997). Here we demonstrate that peptide 46 binds mutant p53. Peptide 46 binding sites were found within both the core and C-terminal domains of p53. Lys residues within the peptide were critical for both p53 activation and core domain binding. The sequence-specific DNA binding of isolated tumor-derived mutant p53 core domains was restored by a C-terminal polypeptide. Our results indicate that C-terminal peptide binding to the core domain activates p53 through displacement of the negative regulatory C-terminal domain. Furthermore, stabilization of the core domain structure and/or establishment of novel DNA contacts may contribute to the reactivation of mutant p53. These findings should facilitate the design of p53-reactivating drugs for cancer therapy.